Do Institutional Investors Demand Public Disclosure? - Bird, Andrew; Karolyi, Stephen A. (Review of Financial Studies, 2016)
We examine the effect of institutional ownership on corporate disclosure policy using a regression discontinuity design. Using a novel dataset comprising every 8-K filing between 1996 and 2006, we find that positive shocks to institutional ownership around Russell index reconstitutions increase the quantity, form, and quality of disclosure. Compared with those at the bottom of the Russell 1000 index, firms at the top of the Russell 2000 index increase institutional ownership by 9.8%, and disclose 4.7% longer 8-K filings with 21.3% more embedded graphics. This incremental disclosure significantly increases the information content of 8-K filings for the market and for analysts. Received July 1, 2015; accepted May 19, 2016 by Editor David Denis.